Quality of Jakarta Smart Card Services in East Jakarta - Retnowati Wahyuning Dyas Tuti; Diah Lina Setyawati; Qiqi Asmara (BASKARA : Journal of Business and Entrepreneurship, 2021)
The purpose of this study was to determine the quality of service Jakarta Smart Card in East Jakarta. This study uses Home Visits Service Quality with indicator: Tangibles, Reliability, Responsive, Assurance, and Empathy. This method used is descriptive qualitative approach. Data collection is done by interview, observation, and documentation. Data analysis uses analysis models from Miles and Huberman, and data validity testing uses triangulation techniques from Moleong. The results of the study stated that the Quality of Smart Jakarta Card Services in East Jakarta has run according to Service Quality theory. Tangibles: facilities and infrastructure used by the school in carrying out the distribution and service of smart Jakarta cards to students is adequate, starting from the computerization and administration system. Reliability: the provision of services in Jakarta Smart Card or operator friendly and efficient in providing services, related to the provision of information about Jakarta Smart Card. Responsive: The school always helps and directs students and parents to all forms of services related to the Jakarta Smart Card and from the results of interviews and observations it can be seen that the operator provides services to students and parents quickly, accurately and responds according to the aspirations of the needs. Assurance: Jakarta Smart Card services are supported by the government. and Empathy: giving or distributing the assistance of the Jakarta Smart Card to students at the Ar-Raisiyah Pharmacy Vocational School in East Jakarta, namely by providing assistance to students who are truly financially unable to reach the target. But in terms of timeliness is still lacking. Needed speed up the thawing process Jakarta Smart Card. Conclusion:  Jakarta Smart Card of sufficient quality service.